ANALISIS CERPEN ZELMANIA KARYA TIKA DITINJAU DARI UNSUR INTRINSIK PSIKOLOGI SASTRA - Desi Karolina Saragih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
In the study of literary psychology, it has an important role in understanding literature because there are several advantages such as the importance of literary psychology to examine more deeply aspects of characterization, with this approach can provide feedback to researchers about the problem of characterization developed, and this kind of research is very helpful for analyzing works literature that is thick with psychological problems. Analyzing the short story literary works with psychological psychology methodology is to determine the id, ego, superego owned by the store in the short story. In this short story id from the main character, Zelmania is Zelmania leaving her husband. Her ego was after a fight with her husband, Zelmania went to Surabaya. The superhero is a Zelmania figure who is aware of his actions that left her husband, all this time her husband always meets his needs, her husband is responsible to him. He wants to go back to his house. Classification is the emotion or feeling felt by the character. We can analyze a short story through what the characters feel. In Zelmania's short story there are some feelings that are felt by the characters. These feelings are revenge and anger, love, disappointment and sadness, hatred, and regret.